THE ROLE OF FOREIGN INVESTMENTS IN THE CONTEXT OF THE COUNTRY’S ECONOMIC DEVELOPMENT - Kalantaryan, Vardan (KATCHAR / ACADEMIA. SOCIAL SCIENCE PERIODICAL, 2025)
In a modern economy, investment activity is one of the main factors of economic development, structural changes and increased competitiveness. A significant part of the countries of the world strive to attract and encourage foreign investments to strengthen productive capacities and sustainable economic development. And for a foreign direct investor, the primary motive for investment is the establishment of long-term relations with the host enterprise, provided that it has a significant influence on its management, as well as increasing profits, reducing taxes, diversifying risks, etc. Currently, the main subjects of foreign direct investment in the global market are international companies and financial groups. However, in reality, foreign direct investment alone cannot guarantee the prosperity of the national economy. The latter, as a development tool, has both its advantages and disadvantages, and in the host country, they contribute to sustainable economic growth only if certain conditions are met. In this regard, the government of the host country is responsible for establishing conditions for foreign direct investment that will contribute to the long-term economic growth of that country, and not only to ensuring the profits of foreign investors. Therefore, the impact of foreign direct investment on the host country depends on many factors, such as the method of entering the market, the sources of financing for direct investment, the latter’s impact on the activities of companies operating in the host country, etc. On the other hand, regardless of the volume of foreign investment, it can also be completely useless and lead to the ruthless waste of the country’s natural resources, as well as the population’s dependence on the outside world for many years. Only with a balanced and considered approach to the joint interests of investors and the host country can it be ensured that foreign investments are effectively attracted and utilised for the benefit of the country’s economic prosperity and the improvement of the population’s living standards.